As dificuldades das mães universitárias da Universidade Federal do Tocantins, Campus de Porto Nacional no período de 2015 a 2020 - Silva, Andrea de Jesus Brito da (Universidade Federal do Tocantins, 2024)
This research analyzed the difficulties of female mothers that study at the Federal University of Tocantins (UFT), Porto Nacional/TO campus, aiming to collaborate with debates on this topic, with the diagnosis of the difficulties faced in the academic environment. The characterization of these student-mothers who were researched sought to show the intricacies of a reality that unfolds among the process of staying during the period of maternity leave and along the academic formation of university courses. The data collected and exposed in this research made it possible to draw a profile of the students who went through the pregnancy process during the research period, with an online questionnaire being carried out to collect information from university mothers in the years of 2015 to 2020. In 2020, due to the pandemic caused by the Coronavirus, we obtained the result of a greater number who used maternity leave, and we obtained answers about the academic path of these university mothers and what were, and if there was, the actions and projects focused on helping them stay at the university and complete their higher education course